DESIGNING FAMILY EDUCATION THROUGH THE RULES OF THE QURAN AND HADITH - Mihrab Afnanda; M. Miftah Arief; Ratu Vina Rohmatika (Journal of Applied Transintegration Paradigm, 2023)
Islamic education should provide young Muslims with the opportunity to learn about their religion. The meaning of education is to develop physical and spiritual potential to obtain certain values ​​and norms. These educational activities can take place in a family, school, or community. The family, school and community are environments that can shape human character. While these three factors influence each other, parenting has the greatest impact on children's education. If the family manages to build a home, the roles of school and community will complement each other. The family is the first and most important environment for a child. This is because the child has a blood bond with his parents that cannot be separated for the rest of his life. Parental consent and parental consent have a large impact on children's behavior. So many moral ailments are caused by the atmosphere of family life. The family is everything to the child. In other words, the picture of the family can be seen from the child's character, habits and morals.